Harnessing in vivo siRNA delivery for drug discovery and therapeutic development - Xie, Frank Y. (Drug Discov Today, 2006)
The use of RNA interference (RNAi) is spreading rapidly to nearly every aspect of biomedical research. The gene silencing capability of RNAi is being used to study individual gene's biological function and role in biochemical pathways. However, the efficacy of RNAi depends upon efficient delivery of the intermediates of RNAi, short interfering RNA (siRNA) and short hairpin RNA (shRNA) oligonucleotides. The delivery challenge is even greater when the aim is to inhibit the expression of target genes in animal models. Although i n vivo delivery of siRNA is complicated and challenging, recent results are encouraging. In this review, the latest developments of in vivo delivery of siRNA and the crucial issues related to this effort are addressed.